PENGEMBANGAN PENUNTUN PRAKTIKUM E-LEARNING KONSEP DASAR IPA SD MAHASISWA PRODI PGSD FIP UNIMED - Fahrur Rozi; Nurhairani Nurhairani; Septian Prawijaya (Universitas Negeri Medan, 2020)
Abstract: The purpose of this study was to develop a practical guide for basic science concepts for PGSD FIP UNIMED students, and to use the Edmodo application to make it easier for students to access learning materials that have been developed. This Practicum Guide is compiled based on the results of observations during lectures that the Practicum Guide used by the lecturer is a textbook that has been used for years and has not been revised according to the current curriculum. This development research uses the 4-D Model consisting of 4 development stages, namely (1) the stage of defining (Define) the objectives of the course by analyzing the Basic Concept of Elementary Science curriculum in accordance with, (2) the planning stage (Design), designing the Basic Concept Practicum Guide Natural Science SD that is in accordance with the demands of the curriculum and improves the ability of students to use technology in accessing lecture Practicum Guides, (3) the development stage (Develop), Designing Practicum Guides Basic concepts of Elementary Science in accordance with the demands of the curriculum and increasing the ability of students to use technology in accessing Guides Practicum lectures, and (4) the dissemination stage (Disseminate) to disseminate existing Practicum Guides to other lecturers in the same KDBK to obtain feedback and input so that better results are obtained. In addition to producing teaching material products, it also provides experience for students and lecturers in carrying out blended learning lectures, furthermore the resulting Practicum Guide will be disseminated in the form of an ISBN book, articles in Scopus indexed proceedings, accredited international or national journals and will be registered as intellectual property.Keywords: Practicum Guide, Science, Elementary SchoolAbstrak: Tujuan Penelitian ini adalah untuk mengembangkan Penuntun Praktikum Konsep Dasar IPA bagi mahasiswa PGSD FIP UNIMED, dan menggunakan aplikasi Edmodo untuk kemudahan mahasiswa untuk mengakses bahan pembelajaran yang telah dikembangkan. Penuntun Praktikum ini disusun berdasarkan hasil observasi pada saat perkuliahan bahwa Penuntun Praktikum yang dipakai dosen adalah diktat yang telah bertahin-tahun digunakan dan belum ada direvisi disesuiakan dengan kurikulum yang ada saat ini. Penelitian pengembangan ini menggunakan Model 4-D terdiri dari 4 tahap pengembangan yaitu (1) tahap pendefinisian (Define) tujuan perkuliahan dengan cara menganalisis kurikulum Konsep Dasar IPA SD yang sesuai dengan, (2) tahap perencanaan (Design), mendesain Penuntun Praktikum Konsep Dasar IPA SD yang sesuai dengan tuntutan kurikulum dan meningkatkan kemampuan mahasiswa dalam menggunakan teknologi dalam mengakses Penuntun Praktikum perkuliahan, (3) tahap pengembangan (Develop), Mendesain Penuntun PraktikumKonsep Dasar IPA SD yang sesuai dengan tuntutan kurikulum dan meningkatkan kemampuan mahasiswa dalam menggunakan teknologi dalam mengakses Penuntun Praktikum perkuliahan, dan (4) tahap penyebaran (Disseminate) mendiseminasikan Penuntun Praktikumyang telah ada kepada dosen lain dalam KDBK yang sama untuk memperoleh feedback dan masukan sehingga diperoleh hasil yang lebih baik. Selain menghasilkan produk bahan ajar, juga memberikan pengalaman kepada mahasiswa dan dosen dalam melaksanakan perkuliahan secara blended learning, selanjutnya Penuntun Praktikumyang dihasilkan akan didesiminasikan dalam bentuk buku berISBN, artikel di prosiding terindeks scopus, jurnal internasional atau nasional terkreditasi dan akan didaftarkan sebagai kekayaan intelektual Kata Kunci: Penuntun Praktikum, IPA, Sekolah Dasar